PROMOTING RELIGIOUS MODERATION VILLAGES ROOTED IN LOCAL WISDOM TO STRENGTHEN RELIGIOUS EDUCATION IN PLURALISTIC COMMUNITIES IN BENGKULU - Pasmah Chandra; Rizkan Syahbudin (Adisam Publisher, 2026)
This study aims to analyze the promotion of religious moderation villages based on local wisdom as a strategy for fostering religious cosmopolitanism in the pluralistic society of Bengkulu. This program leverages the values of tolerance, cooperation, and respect for diversity through an approach rooted in local wisdom that is rich in culture and customs. This approach is considered effective in reducing religion-based conflicts and fostering social harmony. The study employs qualitative methods, including literature review, in-depth interviews, and participatory observation. The findings indicate that the implementation of local wisdom values through the Religious Moderation Village program can enhance public awareness of the importance of diversity and strengthen religious education in building a cosmopolitan way of life. Strategic recommendations are also provided to support the expansion and sustainability of this program. Keywords: Kampung Moderasi, local wisdom, religious cosmopolitanism, pluralistic society, Bengkulu.